Robotic Shoulder Rehabilitation With the Hybrid Assistive Limb in a Patient With Delayed Recovery After Postoperative C5 Palsy: A Case Report - Kubota, Shigeki; Kadone, Hideki; Shimizu, Yukiyo; Takahashi, Hiroshi; Koda, Masao; Miura, Kousei; Watanabe, Hiroki; Suzuki, Kenji; Hada, Yasushi; Sankai, Yoshiyuki; Yamazaki, Masashi (Frontiers in Neurology, 2021)
C5 palsy is a serious complication that may occur after cervical spine surgery; however, standard procedures for shoulder rehabilitation for patients with postoperative C5 palsy have not yet been established. We used a wearable robot suit hybrid assistive limb (HAL) in a patient with delayed recovery after postoperative C5 palsy and conducted shoulder abduction training with the HAL. A 62-year-old man presented with weakness in his left deltoid muscle two days after cervical spine surgery. He experienced great difficulty in elevating his left arm and was diagnosed with postoperative C5 palsy. Seven months after surgery, shoulder abduction training with a HAL was initiated. In total, 23 sessions of shoulder HAL rehabilitation were conducted until 26 months after surgery. His shoulder abduction angle and power improved at every HAL session, and he was able to fully elevate his arm without any compensatory movement after the 23rd session, suggesting that the HAL is a useful tool for shoulder rehabilitation in patients with postoperative C5 palsy. We employed shoulder HAL training for a patient with delayed recovery from postoperative C5 palsy and achieved the complete restoration of shoulder function. We believe that the HAL-based training corrected the erroneous motion pattern of his paralyzed shoulder and promoted errorless motor learning for recovery. Our collective experience suggests that shoulder HAL training could be an effective therapeutic tool for patients with postoperative C5 palsy.